A Systematic Literature Review on the Application of the Philosophy of Science in Addressing Online Gambling Threats : Cybersecurity and Ethical Technology Integration - Danang Danang; Siswanto Siswanto; Greget Widhiati (Jurnal Sains dan Ilmu Terapan, 2024)
This study aims to explore the application of the philosophy of science in developing an ethical, effective, and inclusive cybersecurity model to address the growing threat of online gambling. Using the Systematic Literature Review (SLR) method, 54 articles from reputable databases such as Scopus, IEEE Xplore, SpringerLink, and ScienceDirect were analyzed in-depth. The analysis focused on methodological validity, thematic relevance, contributions to security model development, source credibility, data accessibility, and quality of presented analysis. The results reveal that online gambling platforms leverage technologies such as blockchain, artificial intelligence (AI), and encryption to obscure illegal activities, complicating detection and prevention efforts. As a response, the philosophy of science provides a theoretical foundation to integrate ethical values such as privacy, transparency, and fairness into the development of cybersecurity technologies. Technologies like zero-trust architecture, federated learning, and big data analytics were identified as key tools for building proactive security systems. Furthermore, multistakeholder collaboration among governments, industries, academia, and society is recommended to establish adaptive regulations that foster robust digital security.